Identification and characterization of piperine synthase from black pepper, Piper nigrum L. - Arianne Schnabel (Nature Portfolio, 2021)
Schnabel et al. identify and characterize piperine synthase in developing black pepper fruits which catalyses the formation of piperine from piperoyl coenzyme A and piperidine. A member of BAHD-type acyltransferases, this enzyme can be useful for bio-production of a broad range of medicinally relevant piperamides.